A development model for the agricultural sector of Portugal - Egbert, Alvin C.; Kim, Hyung M. (Baltimore : Published for the World Bank [by] the Johns Hopkins University Press, 1975)
The agricultural sector in Portugal has performed poorly in recent years. The widening gap between agricultural output and domestic demand has led to a rapid rise in imports of food and feed products. An efficiency model, using 1968 base data, was devised for the agricultural sector to evaluate the economic potential of possible investments and new production practices. Investment alternatives included irrigation, livestock herds together with requisite buildings and equipment, pine and eucalyptus forests, tractors and other farm machinery, and new crop alternatives. The analysis demonstrated the interdependence of agricultural investment decisions. Each of the investment alternatives except irrigation appears to have good economic potential in at least one of the regions considered. For example, in one region, four types of investment, farm machinery, dairy, beef, and sheep, were prescribed. In another region, only sheep herd development was prescribed. The total level of investments over the planning period 1968 to 1980 ranged from $40 million to $56 million. It is suggested that country planning groups could improve and continue to use programming models in developing sequential plans.
Includes bibliographical references: p. 95-97.
lje 13/06/17
Loans
Keywords: Agriculture; Agriculture and state